2007
DOI: 10.1260/1478-0771.5.2.356
|View full text |Cite
|
Sign up to set email alerts
|

Digital Resource Semantic Management of Islamic Buildings Case Study on Isfahan Islamic Architecture Digital Collection

Abstract: This article describes an innovative way to facilitate and to provide a collaborative semantic management of digital resources of Islamic historical buildings. The approach combines a topic maps-based semantic support to the 5W1H model (Where, Who, When, What, Who and How) with objective of enabling comprehensive semantics of digital contents for research and education purposes. The topic mapsbased semantic support enables to reduce the problems of semantic gaps among different communities (cultural, linguisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Their classification system is based on the number of folds by which an image is characterized and the image's fundamental region and class. Okamura et al (2007)) have likewise established semantic digital resources of Islamic historical buildings focusing on Islamic architecture in Isfahan, Iran. Their research work revealed that a topic maps-based semantic model applied to collaborative metadata management paradigms can be easily exploited as a tool to enhance traditional architectural design and interdisciplinary studies.…”
Section: Introductionmentioning
confidence: 99%
“…Their classification system is based on the number of folds by which an image is characterized and the image's fundamental region and class. Okamura et al (2007)) have likewise established semantic digital resources of Islamic historical buildings focusing on Islamic architecture in Isfahan, Iran. Their research work revealed that a topic maps-based semantic model applied to collaborative metadata management paradigms can be easily exploited as a tool to enhance traditional architectural design and interdisciplinary studies.…”
Section: Introductionmentioning
confidence: 99%